Emergency Psychiatric Consultations During and After the COVID-19 Lockdown in Italy. A Multicentre Study - Balestrieri, Matteo; Rucci, Paola; Amendola, Davide; Bonizzoni, Miki; Cerveri, Giancarlo; Colli, Chiara; Dragogna, Filippo; Ducci, Giuseppe; Elmo, Maria Giuseppa; Ghio, Lucio; Grasso, Federico; Locatelli, Clara; et al. (Frontiers in Psychiatry, 2021)
Aims: The aim was to analyse the psychiatric consultations in nine Italian hospital emergency departments, by comparing the lockdown and post-lockdown periods of 2020 with the equivalent periods of 2019. Methods: Characteristics of psychiatric consultations, patients, and drug prescriptions were analyzed. Joinpoint models were used to identify changes in the weekly trend of consultations. Results: A 37.5% decrease in the number of consultations was seen during the lockdown period and 17.9% after the lockdown. The number of individual patients seen decreased by 34.9% during the lockdown and 11.2% after the lockdown. A significant change in the number of consultations from week 11 to week 18 occurred, followed by a gradual increase. There was a higher percentage of patients with previous psychiatric hospitalizations during the lockdown period (61.1 vs. 56.3%) and a lower percentage after the lockdown (59.7 vs. 64.7%). During the lockdown there was a large increase in psychiatric consultations for substance use disorders, whereas more consultations for manic episodes occurred after the lockdown. A 3.4% decrease was observed in consultations for suicidal ideation and planning during the lockdown, followed by an upward rebound after the lockdown, along with an increase in consultations for suicide attempts. During lockdown antipsychotic and benzodiazepine prescriptions increased by 5.2 and 4.1%, respectively. After the lockdown, the number of compulsory hospitalizations was higher than in 2019. Conclusions: We observed a decrease of psychiatric consultations during and after the lockdown. There was an increase in consultations for manic episodes and suicidality after the lockdown. The focus of psychiatric services must remain high particularly in this latter period.